ARNT-dependent HIF-2α signaling protects cardiac microvascular barrier integrity and heart function post-myocardial infarction - Karim Ullah; Lizhuo Ai; Yan Li; Lifeng Liu; Qin Zhang; Kaichao Pan; Zainab Humayun; Lin Piao; Albert Sitikov; Qiong Zhao; Qiaozhu Su; Willard Sharp; et al. (Communications Biology)
Abstract Myocardial infarction (MI) compromises the cardiac microvascular endothelial barrier, increasing leakage and inflammation. HIF2α, predominantly expressed in cardiac endothelial cells during ischemia, has an unclear role in barrier function during MI. Here, we show that inducible, adult endothelial-specific deletion of Hif2α in mice leads to increased mortality, cardiac leakage, inflammation, reduced heart function, and adverse remodeling after MI. In parallel, human cardiac microvascular endothelial cells (HCMVECs) lacking HIF2α display impaired barrier integrity, reduced tight-junction proteins, increased cell death, and elevated IL-6 levels, effects that are alleviated by overexpressing ARNT, a key partner of HIF2α under hypoxic conditions. Interestingly, ARNT, but not HIF2α, directly binds the IL-6 promoter to suppress its expression. These findings suggest the HIF2α/ARNT axis as a protective mechanism in heart failure post-MI and identify potential therapeutic targets to support cardiac function.